A study of delayed purchases of enabling products in the United States: the case of hearings aids. (July 2015) - Moschis, George P.; Lee, Euehun; Mathur, Anil; E. Rigdon, Edward; Kwai Fatt, Choong
ABSTRACT Although hearing loss afflicts millions of adults globally, most of them elderly, a relatively small percentage of them purchase hearing aids, and buyers regularly delay purchase for years. This study provides explanations for the likelihood and timing of the purchase of hearing aids. Data from a large‐scale national mail survey of 507 hearing‐impaired persons in the United States reveal that consumers do not make decisions in a time vacuum or in isolation from previous life experiences. Rather, their hearing aid purchase decision is time dependent, and time exerts different effects on consumers depending on their stage in life. Because hearing impairment is a condition experienced by consumers globally, the study findings have implications for theory and practice worldwide.